Development of New Rendemen Formula as an Effort to Control the Performance of Sugar Factory - Bambang A. Santoso; Toto Martoyo; Subhanuel Bahri (IPTEK The Journal for Technology and Science, 2009)
Based on the data of sugar factory performance in Java during 1936-1940 and 1956-2000 milling season periods, there are three important factors that can control contribution of each sector at sugar fac-tory and absolutely affect targeted rendemen. Those fac-tors include cane pol in the field, harvesting efficiency and factory efficiency. Cane pol in the field is a result of plantation sector performance. Harvesting efficiency re-presents the performance of harvesting sector, while fac-tory efficiency has relationship with the performance of factory itself. In this research, the standard of factory performance was the data of factory performance in the milling season from 1936 to 1940 and the factory perfor-mance tested was the data of factory performance in the 1956-2000 milling season period. The aim of this research was to obtain a formula of rendemen calculation that represents a performance of all production aspects at sugar factory. The formula used for rendemen calculati-on was Rendemen (%) = cane pol in the field (%) x har-vesting efficiency (%) x factory efficiency (%) x 10-4. By using this concept, it is expected that targeted rendemen can be achieved since this concept can control all stages of production using the standard of each production aspect.